Road or Rail? The partisan politics of urban transport policy in the Australian States - Phillimore, John; Fenna, Alan (Wiley-Blackwell, 2020)
This paper addresses the question of “what is ‘Labor’ about state Labor governments?” by comparing the policies of the two sides of politics in respect of public transport. It postulates a clear difference that should be manifest in Labor’s preference for rail and the Coalition’s preference for roads. To test that proposition it conducts a longitudinal comparison within one state (Western Australia) and triangulates that by surveying across jurisdictions.